Minimally Invasive Percutaneous Leverage Reduction in the Treatment of Pediatric Salter–Harris IV and V Distal Femoral Physeal Fractures - Wen Shu; ZiXuan Ou; QiYuan Feng; Haobo Zhong; Xin Tang (Orthopaedic Surgery, 2024)
Objective Distal femoral physeal fractures (DFPF) are rare but severe injuries in children, and there is no consensus on treatments for Salter–Harris (S–H) IV and V type of DFPF yet. This study aimed to introduce a minimally invasive technique using percutaneous leverage reduction combined with Kirschner wires fixation in treating pediatric DFPF with S–H IV and V type of injury and evaluate the clinical results. Methods From July 2008 to June 2018, the authors' institute (Union Hospital, Tongji Medical College) retrospectively reviewed all patients diagnosed with pediatric DFPF. They were divided into two groups according to received treatment: children in the minimally invasive technique group were treated with a minimally invasive percutaneous leverage reduction technique, and the traditional technique group included the other children who received the conventional open reduction with internal fixation (ORIF). The surgical and clinical results of the two groups were collected and analyzed. The independent sample t‐test analysis and the chi‐square test were applied to compare continuous and categorical variables. Results A total of 14 pediatric patients were recruited, including five females and nine males with DFEF. All eight patients in the minimally invasive technique group and four of the six patients in the ORIF group were treated successfully. One patient in the minimally invasive technique group opted for conservative treatment due to his good functional recovery, while the other two patients in the ORIF group needed further surgery because of the limb length discrepancy. There was a difference in surgery duration (p < 0.001), intraoperative fluoroscopy numbers (p = 0.006), intraoperative blood loss (p < 0.001), radiological union time (p = 0.003) and knee flexion angle (p < 0.001) between two groups. Patients in the minimally invasive technique group all received total knee society (KSS) scores, while the average scores in the ORIF group were lower (100.00 vs. 97.67). Conclusion The minimally invasive technique is better than conventional ORIF in terms of surgery duration, intraoperative blood loss, radiological union time, knee flexion angle and average KSS score. This percutaneous leverage reduction technique might be a good alternative for treating S–H IV and V DFPF in children.